FAN FICTION BETWEEN PLAGIARISM AND ORIGINAL WORK - Ruxandra VIȘOIU (Challenges of the Knowledge Society, 2025)
Fan fiction, as the name suggests, represents creations based on already existing works. But their authors are often not professional writers, but fans, sympathizers of the original work, who put their own stamp on the new work: they modify the narrative thread, the characters, the era in which the events take place, all with a desire to continue the pleasure of reading or to present their own version of the work, giving free rein to the imagination. Can works of fan fiction be original creations? Or do we consider them all copycats or work of actual plagiarism? Do they fall into the category of derivative work or pastiche, a slightly outdated term, but quite similar in meaning to this new type of predominantly digital work? We will try to address all these topics in the present work, along with the implications of AI (AI) in the development of fan fiction and some de lege ferenda proposals on this topic.